Analisis Brand Image, Iklan dan Kualitas Produk dalam Menentukan Loyalitas Pelanggan dengan Brand Community Sebagai Variabel Intervening - Ashyfa Agnia; Ade Komaludin; Yusuf Abdullah (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to test the effect brand image, advertising and product quality on customer loyalty with brand community as an intervening variable. The study was conducted on AREI members outdoor community in East Priangan. Sampling is carried out using techniques propotioned stratified random sampling, with a sample size of 250, spread across store Tasikmalaya and Garut. The research instrument used was a questionnaire with a Likert scale. The analysis technique used is structural equation modeling with the smartPLS application. The results of this research show that 1) Brand image, advertising, products, brand community and customer loyalty, in excellent condition; 2) Brand image, advertising and product quality have a positive and significant effect on brand community; 3) Brand image, advertising and product quality have a positive and significant effect on customer loyalty; 4) Brand community positive and significant effect on customer loyalty; 5) Brand image, advertising and product quality influence customer loyalty through the brand community.